Pelatihan Menulis Paragraf Persuasif Sebagai Upaya Menguatkan Kecakapan Berpikir Kritis dalam Menyampaikan Gagasan Bagi Pengurus Dan Anggota Majelis Taklim Qur’ani Nurul Fattah Serpong, Tangerang Selatan - Riastri Novianita; Bobby Octavia Yuskar; Athiy Dina Rosihana; Ondy (Assoeltan: Indonesian Journal of Community Research and Engagement, 2025)
Writing is a fundamental skill that is crucial in both academic and everyday life. One strategic writing skill is writing persuasive paragraphs. Persuasive paragraphs require not only the ability to construct well-formed sentences, but also the ability to construct logical, convincing, and relevant arguments. Through persuasive paragraphs, one can convey ideas more effectively, while simultaneously practicing critical thinking skills in developing reasons and supporting evidence. However, many students still struggle to compose good persuasive paragraphs. These challenges typically arise from a lack of writing practice, limited insight into argumentation techniques, and a limited understanding of the logical structure of conveying ideas. As a result, many pieces of writing are purely descriptive without incorporating elements of critical analysis or strong persuasive power. In this fast-paced and competitive digital era, persuasive writing skills are becoming increasingly important. This ability is not only useful in academic contexts, such as writing.